Atomoxetine in the treatment of children, adolescents and adults with attention deficit hyperactivity disorder. Issue 1 (January 2006) - Turgay, Atilla
Atomoxetine hydrochloride (Strattera ®® ), a selective norepinephrine reuptake inhibitor, was the first nonstimulant approved by the US Food and Drug Administration in November 2002, for the treatment of attention deficit hyperactivity disorder (ADHD) in children, adolescents and adults (6 years of age through to adulthood). Atomoxetine is not a controlled substance in the USA or Canada. This article outlines the pharmacology, pharmacokinetics, clinical efficacy and safety of atomoxetine and compares its potential use with other ADHD medications. Recommendations for future research are also made. The efficacy and safety studies of atomoxetine in adults with ADHD led to its approval in the USA and Canada for use in adult ADHD. Among other ADHD medications, atomoxetine has the longest duration of effects. It does not disturb sleep or have potential for abuse. The effectiveness of atomoxetine in managing hyperactivity, impulsivity, inattention, self-esteem, interpersonal and family relationships, and the overall functioning of subjects has been well established in several studies using appropriate scientific methodologies and reliable and valid instruments measuring effectiveness and side effects. The literature provides support for the use of atomoxetine in treating patients with ADHD with diversion and abuse of ADHD medications, tics, anxiety, enuresis, sleep disorders and depressive symptoms. The most common side-effects are appetite suppression, nausea and somnolence in the initial treatment phases. Atomoxetine seems to be well tolerated with a very low discontinuation ratio associated with few side-effects. Future studies may further describe the use and efficacy of atomoxetine in many complicated areas of ADHD and its comorbidities. The combined use of atomoxetine and psychostimulants is a burgeoning area for further research. Atomoxetine may be considered to be the first of a new generation of nonstimulant treatments for ADHD approved for treatment.